UNVEILING THE COLONIAL IMPACT ON MUKYMI’S LITERARY LEGACY - Firdavs Kazakov Farhod ugli (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation:This article explores the complex legacy of Uzbek poet Mukimi (1850-1903) and the challenges of understanding his work in its historical context. It argues that Soviet interpretations of Mukimi were shaped by ideology, downplaying his religious themes and social critique. With Uzbek independence, scholars began to re-evaluate Mukimi's work, highlighting the influence of Russian colonialism and the importance of textual criticism to recover his original voice. The article concludes by emphasizing the enduring relevance of Mukimi's poetry, which grapples with timeless themes and offers a counterpoint to the materialism of today's world.